2019
DOI: 10.14744/ijmb.2019.04127
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency status in Turkey: A meta-analysis

Abstract: INTERNATIONAL JOURNAL OF MEDICAL BIOCHEMISTRY Meta Analysis Vitamin D deficiency status in Turkey: A meta-analysis V itamin D is a steroid hormone that has a major role in bone mineralization through the regulation of calcium and phosphorus metabolism. The main sources of vitamin D are cutaneous synthesis and the ingestion of food, especially fish oil, eggs, and liver [1]. The most common forms of vitamin D absorption are vitamin D2 (ergocalciferol) and vitamin D3 (cholecalciferol). Vitamin D3 is synthesized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 34 publications
2
31
4
2
Order By: Relevance
“…Likewise, in a meta-analysis, including 40 studies with 111,582 sample sizes published in 2019, vitamin D deficiency was shown as <20 ng/mL. [ 10 , 11 ] In our study, the mean age was 57 years and the mean vitamin D level was 21 ng/mL. The vitamin D level was >20 ng/mL in 56%, while <20 ng/mL in 44% of patients.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Likewise, in a meta-analysis, including 40 studies with 111,582 sample sizes published in 2019, vitamin D deficiency was shown as <20 ng/mL. [ 10 , 11 ] In our study, the mean age was 57 years and the mean vitamin D level was 21 ng/mL. The vitamin D level was >20 ng/mL in 56%, while <20 ng/mL in 44% of patients.…”
Section: Discussionsupporting
confidence: 57%
“…Vitamin D deficiency was common among the adult Turkish population. [ 10 , 11 ] However, higher vitamin D levels than expected in individuals at risk for vitamin D deficiency, especially in post-menopausal women, maybe due to frequent visits to the hospitals due to chronic diseases, such as hypertension or hyperlipidemia, allowing detection of vitamin D deficiency and vitamin D replacement in these patients. In addition, vitamin D replacement is used more widely in the elderly population as a part of treatment for osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis, it was stated that 64.7% of Turkish women had vitamin d deficiency (9). In this study, serum vitamin D deficiency was present in more patients (97.3%) compared to vitamin D deficiency observed in the community (9).…”
Section: Discussionmentioning
confidence: 57%
“…In their study, which included 63 TE patients, Karadağ et al showed that serum vitamin D levels were lower in TE patients than in the control group (8). Vitamin D deficiency is a common condition in the community (9). In a meta-analysis, it was stated that 64.7% of Turkish women had vitamin d deficiency (9).…”
Section: Discussionmentioning
confidence: 99%